Inhibitory effect on Streptococcus mutans and mechanical properties of the chitosan containing composite resin - Ji-Sun Kim; Dong-Hoon Shin (Korean Academy of Conservative Dentistry, 2013)
Objectives This study evaluated the antibacterial effect and mechanical properties of composite resins (LCR, MCR, HCR) incorporating chitosan with three different molecular weights (L, Low; M, Medium; H, High). Materials and Methods Streptococcus (S). mutans 100 mL and each chitosan powder were inoculated in sterilized 10 mL Brain-Heart Infusion (BHI) solution, and was centrifuged for 12 hr. Absorbance of the supernatent was measured at OD660 to estimate the antibacterial activities of chitosan. After S. mutans was inoculated in the disc shaped chitosan-containing composite resins, the disc was cleansed with BHI and diluted with serial dilution method. S. mutans was spread on Mitis-salivarius bacitracin agar. After then, colony forming unit (CFU) was measured to verify the inhibitory effect on S. mutans biofilm. To ascertain the effect on the mechanical properties of composite resin, 3-point bending and Vickers hardness tests were done after 1 and 3 wk water storage, respectively. Using 2-way analysis of variance (ANOVA) and Scheffe test, statistical analysis was done with 95% significance level. Results All chitosan powder showed inhibition effect against S. mutans. CFU number in chitosan-containing composite resins was smaller than that of control resin without chitosan. The chitosan containing composite resins did not show any significant difference in flexural strength and Vickers hardness in comparison with the control resin. However, the composite resin, MCR showed a slightly decreased flexural strength and the maximum load than those of control and the other composite resins HCR and LCR. Conclusions LCR and HCR would be recommended as a feasible antibacterial restorative due to its antibacterial nature and mechanical properties.